Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3233/jad-215065
|View full text |Cite
|
Sign up to set email alerts
|

A Primer on the Evolution of Aducanumab: The First Antibody Approved for Treatment of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common form of dementia with global burden projected to triple by 2050. It incurs significant biopsychosocial burden worldwide with limited treatment options. Aducanumab is the first monoclonal antibody recently approved by the US-FDA for mild AD through the accelerated approval pathway. It is the first molecule to be approved for AD since 2003 and carries with it a therapeutic promise for the future. As the definition of AD has evolved from a pathological entity to a clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…The cholinesterase inhibitors and the glutamate NMDA receptor antagonist memantine that have been approved for the treatment provide symptomatic relief for only a fraction of AD patients [ 9 , 82 , 83 ]. The beneficial effects of recently approved disease modifying Aβ monoclonal antibody Aducanumab on AD patients remain to be determined [ 84 , 85 ]. Some earlier studies have shown that PLGA nanoparticles functionalized with various drugs/agents such as donepezil, galantamine, quercetin, memantine and curcumin can exhibit beneficial effects on cellular and/or animal models of AD compared to cells/mice treated with drugs alone or vehicles used for dissolving drugs/PLGA nanoparticles [ 37 , 39 , 40 , 67 , 69 , 70 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cholinesterase inhibitors and the glutamate NMDA receptor antagonist memantine that have been approved for the treatment provide symptomatic relief for only a fraction of AD patients [ 9 , 82 , 83 ]. The beneficial effects of recently approved disease modifying Aβ monoclonal antibody Aducanumab on AD patients remain to be determined [ 84 , 85 ]. Some earlier studies have shown that PLGA nanoparticles functionalized with various drugs/agents such as donepezil, galantamine, quercetin, memantine and curcumin can exhibit beneficial effects on cellular and/or animal models of AD compared to cells/mice treated with drugs alone or vehicles used for dissolving drugs/PLGA nanoparticles [ 37 , 39 , 40 , 67 , 69 , 70 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, the China Food and Drug Administration (CFDA) approved Sodium Oligomannate for the treatment of mild-moderate AD, which can effectively improve the cognitive function of AD patients and delay the progression of the disease [21][22][23]. In 2021, the U.S. FDA approved Aducanumab for the early treatment of AD, which can reduce Aβ deposition and tau phosphorylation and delay disease progression [24], all of which demonstrate that early diagnosis is important for AD patients. Therefore, we advise that physicians should put more effort into introducing the signi cance of early diagnosis and obtain patients' understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Aducanumab, gantenerumab, and BAN2401 all bind primarily to insoluble and soluble aggregates [28]. A major drawback in the current clinical trials of passive immunotherapy is the lack of specific targeting in most toxic Aβ oligomers, for example, aducanumab and gantenerumab bind to Aβ fibrillation or aggregates, while crenezumab can recognise different Aβ forms [90][91][92][93]. Through the 'peripheral sink' hypothesis, the antibody that targets soluble Aβ may play a role in the preclinical stages of AD.…”
Section: Differential Selectivity In Aβ Oligomersmentioning
confidence: 99%